Pentingnya pendidikan Islam dalam membentuk karakteristik anak - Permatasari, Inda (Maliki Interdisciplinary Journal, 2024)
The impotent of Islamic education in shaping children’s character is a very big hope for society to make a child who can get a good education and character, so that he becomes a man of character, has a noble personality, and can live a life in accordance with Islamic law. Islamic education in essence is as a vehicle for the formation of human character with high morality. In Islamic teachings, morality or morality cannot be separated from faith. Faith is an acknowledgment of the heart in believing in Allah SWT. Education is very important for children because it can educate children to achieve their dreams. One of the educations that are planted from an early age is religious education, especially Islamic education for us as Muslims.